2017
DOI: 10.1590/1414-431x20176227
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin inhibits oxidization-induced differentiation of T helper cells through inhibiting costimulatory CD40 and CD80

Abstract: Adiponectin is a multifunctional adipokine that has several oligomeric forms in the blood stream, which broadly regulates innate and acquired immunity. Therefore, in this study, we aimed to observe the differentiation of T helper (Th) cells and expression of costimulatory signaling molecules affected by adiponectin. The mRNA and protein expression levels of adiponectin and its receptors in oxidized low density lipoprotein cholesterol-treated endothelial cells were assayed by real time PCR and immunofluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, Surendar and colleagues found that the stimulation of naïve CD4+ cells with adiponectin leads to a reduced number of IFN-γ+ T cells [ 83 ]. Similarly, a separate study showed that adiponectin suppresses the ox-LDL-induced differentiation of Th1 and Th17 cells [ 84 ]. Additionally, in line with previous studies, Zhang et al found that adiponectin suppressed the Th1 and Th17 cytokines IFN-γ and IL-6, respectively [ 85 ].…”
Section: Adiponectinmentioning
confidence: 99%
“…Furthermore, Surendar and colleagues found that the stimulation of naïve CD4+ cells with adiponectin leads to a reduced number of IFN-γ+ T cells [ 83 ]. Similarly, a separate study showed that adiponectin suppresses the ox-LDL-induced differentiation of Th1 and Th17 cells [ 84 ]. Additionally, in line with previous studies, Zhang et al found that adiponectin suppressed the Th1 and Th17 cytokines IFN-γ and IL-6, respectively [ 85 ].…”
Section: Adiponectinmentioning
confidence: 99%
“…It has been demonstrated that adiponectin markedly increases T-box transcription factor T-bet 115 and ROR-γt 116 expression in CD4 + T cells indicating that this adipokine enhances the differentiation to Th1 and Th17 phenotype, respectively. On the other hand, Xiao et al 117 suggested that adiponectin may suppress the differentiation of Th1 and Th17 from CD4 + T lymphocytes through inhibition of costimulatory molecules involved in this process, that is, CD80 and CD40. These observations were further confirmed by Zhang et al 118 who demonstrated that treatment of CD4 + T cells with adiponectin inhibited the differentiation to Th1…”
Section: Adipokines Modulate the Activity Of Cells Engaged In Innatmentioning
confidence: 99%
“…In particular, exogenous adiponectin inhibited IFN‐γ during Th1 cell differentiation and downregulated the Th17 cytokines during Th17 cell differentiation, which was mediated through the SIRT1‐PPARγ‐RORγt pathway 78 . Moreover, adiponectin was found to inhibit the differentiation of Th1 and Th17 cells through AdipoR1, resulting in the downregulation of CD80 and CD40, and suppressing antigen presentation to inhibit the differentiation of Th1 and Th17 cells in vitro 79 …”
Section: Adiponectin In Adaptive Immune Cellsmentioning
confidence: 98%
“…78 Moreover, adiponectin was found to inhibit the differentiation of Th1 and Th17 cells through AdipoR1, resulting in the downregulation of CD80 and CD40, and suppressing antigen presentation to inhibit the differentiation of Th1 and Th17 cells in vitro. 79 Tregs that exert anti-inflammatory effects are severely reduced in fatty tissue in obese and IR states. New evidence indicates that g-APN impacts the capacity of Tregs to produce IL-10 and induces the expression of Forkhead box P3 (FOXP3).…”
Section: Adiponectin In Adaptive Immune Cellsmentioning
confidence: 99%